2003
DOI: 10.1210/me.2003-0148
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X Receptor Is a Nonsilent Major Contributor to Vitamin D Receptor-Mediated Transcriptional Activation

Abstract: The vitamin D receptor (VDR) belongs to the thyroid hormone/retinoid receptor subfamily of nuclear receptors and functions as a heterodimer with retinoid X receptor (RXR). The RXR-VDR heterodimer, in contrast to other members of the class II nuclear receptor subfamily, is nonpermissive where RXR does not bind its cognate ligand, and therefore its role in VDR-mediated transactivation by liganded RXR-VDR has not been fully characterized. Here, we show a unique facet of the intermolecular RXR-VDR interaction, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
52
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 23 publications
4
52
0
Order By: Relevance
“…It has been demonstrated that RXR is an essential partner of VDR and actively participates in VDR-dependent gene expression [31]. Similar observations that RXR is a significant contributor to VDR-mediated gene expression have been reported elsewhere [32]. Notably, our transfection data demonstrated that retinoid alone can activate RXRα/VDR heterodimers on the ER6 response element of CYP3A4 gene.…”
Section: Discussionsupporting
confidence: 90%
“…It has been demonstrated that RXR is an essential partner of VDR and actively participates in VDR-dependent gene expression [31]. Similar observations that RXR is a significant contributor to VDR-mediated gene expression have been reported elsewhere [32]. Notably, our transfection data demonstrated that retinoid alone can activate RXRα/VDR heterodimers on the ER6 response element of CYP3A4 gene.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, we found that the baseline GFP-VDR distribution in ROS17/2.8 (A1G) cells was predominantly cytoplasmic (>70%), a finding that confirms what others have reported for VDR distribution in ROS 17/2.8 cells [Racz and Barsony, 1999], COS-1 (Sunn et al, 2001), and COS-7 [Racz andBarsony, 1999] kidney cells, and microwave-fixed fibroblasts [Barsony et al, 1990]. Next, [Fleet, 2004], including Caco-2 cells [Wali et al, 1992;Tien et al, 1993;Bettoun et al, 2003]. However, our inability to see membrane-associated GFP-VDR could reflect several factors including low sensitivity of the method to detect the 1-3% of VDR that is proposed to be associated with the membrane or an inability of the GFP-VDR to associate with the membrane.…”
supporting
confidence: 89%
“…Our observation is consistent with what Barsony et al [1997] reported using a BODIPY-labeled 1,25(OH) 2 D 3 in human fibro-blasts. This does not support a role for a membrane-associated VDR as the mediator responsible for the activation of various kinases and signal transduction pathways by 1,25(OH) 2 D 3 that have been observed in a variety of cell types [Fleet, 2004], including Caco-2 cells [Wali et al, 1992;Tien et al, 1993;Bettoun et al, 2003]. However, our inability to see membrane-associated GFP-VDR could reflect several factors including low sensitivity of the method to detect the 1-3% of VDR that is proposed to be associated with the membrane or an inability of the GFP-VDR to associate with the membrane.…”
Section: Discussionmentioning
confidence: 72%
“…Effect of U0126 on DNA Binding and Subcellular Localization-If active RXR is the limiting factor in MC3T3-E1 cells, then treatment with U0126 should enhance VDR binding to DNA as the VDR/RXR heterodimer binds more stably to DNA than does a VDR dimer (57). Thus, to determine whether U0126 treatment altered DNA binding, nuclear extracts were prepared from MC3T3-E1 and HeLa cells treated with U0126 or not in the presence or absence of 1,25-D and EMSA were performed.…”
Section: Differential Regulation Of Vdr Activity In Mc3t3-e1 Cells Ismentioning
confidence: 99%